The Effect of Environmental Social Governance, Cash Holding and Capital Structure on Financial Performance - Fauziyah, Rifa; Paramita, Veronika Santi (Commercium : Journal of Business and Management, 2025)
The study aims to determine the influence of Environmental Social Governance (ESG), cash holding, and capital structure on the financial performance of energy sector companies listed on the Indonesia Stock Exchange. The research method is quantitative with descriptive causality analysis. The population in this study is all 83 energy sector companies listed on the Indonesia Stock Exchange, with purposive sampling criteria, with a sample of 12 companies. The analysis method used is panel data regression. Partially, ESG and DAR do not affect ROA, cash holding has a positive effect on ROA. Simultaneously, all three variables impact ROA (financial performance). Energy sector companies need to re-evaluate their overall performance, such as allocating costs to implement ESG, managing cash optimally and wisely, and using sufficient debt to improve financial performance.